Research and demonstration on hydrogen compatibility of pipelines: a review of current status and challenges. (1st August 2022) - Wang, Hantong; Tong, Zhi; Zhou, Guijuan; Zhang, Ci; Zhou, Hongyu; Wang, Yao; Zheng, Wenyue
Abstract: Hydrogen transportation by pipelines gradually becomes a critical engineering route in the worldwide adaptation of hydrogen as a form of clean energy. However, due to the hydrogen embrittlement effect, the compatibility of linepipe steels and associated welds with hydrogen is a major concern when designing hydrogen-carrying pipelines. When hydrogen enters the steels, their ductility, fracture resistance, and fatigue properties can be adversely altered. This paper reviews the status of several demonstration projects for natural gas-hydrogen blending and pure hydrogen transportation, the pipeline materials used and their operating parameters. This paper also compares the current standards of materials specifications for hydrogen pipeline systems from different parts of the world. The hydrogen compatibility and tolerance of varying grades of linepipe steels and the relevant testing methods for assessing the compatibility are then discussed, and the conservatism or the inadequacies of the test conditions of the current standards are pointed out for future improvement. Graphical abstract: Image 1 Highlights: Summarized projects of pure-hydrogen and natural gas-hydrogen blending pipelines. Discussed the factors affecting hydrogen compatibility of pipeline. Reviewed the testing methods for assessing hydrogen-steel compatibility. Presented a new proposal for toughness test for pipeline slow loading condition. Several challenges facing the high-pressure hydrogen pipelines are outlined.